Misool Baseftin Foundation's Financial Performance Doubled in Five Years - Ferdinant Nuru; Fredy Arios Tiblola; Yohanis Eduard Rijoli (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
Measuring and controlling performance within non-profit organizations can be seen as a strong tool for feedback and learning for the company and a way to evaluate impacts, results, and outputs. To determine and analyze the financial performance of nonprofit organizations at the Misool Baseftin Foundation for the 2016–2020 period, Ritchie and Kolodinsky's (2003) financial ratio analysis, which includes financial performance ratios, public support ratios, and fundraising efficiency ratios, was used. (Effectiveness of fundraising). Secondary data from the Foundation's financial accounts is what is referred to as research data. Descriptive quantitative techniques are used in the research process. The analysis's findings demonstrate that (1) total income to total assets is over 1.0, with the average ratio sitting at 2.03, indicating very high financial performance. (2) For the past five years, the ratio of total income minus total costs to total assets is 0.04. A positive value means that revenue in that year exceeded costs and that a significant percentage was saved as an asset. Therefore, the performance of nonprofit organizations improves as this ratio increases.